Kajian Konsentrasi Pati Singkong Karet (Manihot glaziovii) dan Penambahan Fraksi Oleat dan Asam Oleat pada Karakteristik Fisik dan Barrier Edible Film - Anik Wahyuningsih; Damat Damat; Warkoyo Warkoyo (Food Technology and Halal Science Journal, 2019)
The edible film can be an alternative packing of safe and biodegradable products. The utilization of Ceara rubber starch (Manihot glaviovii) as an edible film making material with the addition of oleic fraction and oleic acid is expected to improve the characteristic of starch-based edible film. The purpose of this study are: (i) to know the existence of interaction between the treatment of Ceara starch concentration and addition of oleic fraction and oleic acid on physical characteristics and barrier of edible film, (ii) to know the effect of treatment of Ceara starch concentration on physical characteristics and barrier of edible film, and (iii) to know the effect of oleic fraction and oleic acid addition on physical characteristics and barrier of edible film. This research uses Randomized Completely Block Design (RCBD) factorial composed of two factors. The first factor was the difference in the concentration of the ceara rubber starch consisting of 3 levels (3%, 4%, and 5%) and the second factor was the addition of lipids (0% lipid, 15% RBDPO, and 15% oleic acid (w/w polymer)) with 3 repetitions. Parameters measured were thickness, transparency, water vapor transmission rate (WVTR), elasticity, tensile strength, solubility, and microstructure of the edible film. The results showed that there was an interaction between the concentration of ceara rubber starch with the lipid addition of in WVTR, elasticity, and tensile strength parameter of edible film. The concentration of ceara rubber starch has a significant effect on the parameters of thickness, transparency, and solubility. The addition of lipids significantly affected the parameters of thickness, transparency, and WVTR. The best treatment was obtained P2A3 (4% ceara rubber starch + 15% oleic acid) with an average thickness of 0,133 mm, transparency 0,818 a/mm, 17,246 g/m2.day water vapor transmission rate, 48,781% elasticity, tensile strength 1,458 MPa, and 44.035% solubility.